2018
DOI: 10.1038/s41419-018-0513-1
|View full text |Cite
|
Sign up to set email alerts
|

Translational attenuation and retinal degeneration in mice with an active integrated stress response

Abstract: An integrated stress response (ISR), identified in several different animal models of inherited retinal degeneration (IRD), is activated following various cellular stresses. The ISR results in the phosphorylation of eIF2α (p-eIF2α) and a consequent halt in protein synthesis. Although generally protective, persistent elevations in p-eIF2α could lead to cell demise. Therefore, we aimed to determine whether ISR activation is associated with diminished translation rates in mice with IRD. Retinal protein extracts f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
53
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(60 citation statements)
references
References 32 publications
5
53
1
Order By: Relevance
“…There are no known roles of eIF2α other than protein synthesis regulation, so it has been assumed that its phosphorylation leads to a substantial attenuation in protein synthesis rates, but no study has functionally and genetically modulated p-eIF2α in degenerating retinas and subsequently assessed retinal protein synthesis rates and photoreceptor survival. In addition, as we have proposed previously 1 , eIF2α may not be the primary point of translational control in degenerating retinas. Those findings make us question what role, if any, eIF2α phosphorylation plays in retinal degeneration.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…There are no known roles of eIF2α other than protein synthesis regulation, so it has been assumed that its phosphorylation leads to a substantial attenuation in protein synthesis rates, but no study has functionally and genetically modulated p-eIF2α in degenerating retinas and subsequently assessed retinal protein synthesis rates and photoreceptor survival. In addition, as we have proposed previously 1 , eIF2α may not be the primary point of translational control in degenerating retinas. Those findings make us question what role, if any, eIF2α phosphorylation plays in retinal degeneration.…”
Section: Introductionmentioning
confidence: 65%
“…Inherited retinal degeneration (IRD) is a class of retinal dystrophies in which there is currently no cure and few treatment options available. Activation of the unfolded protein response (UPR) has been detected in multiple animal models of retinal degeneration 1–5 . The UPR is a series of signaling events following endoplasmic reticulum (ER) stress and is signaled through three ER – resident membrane proteins, protein kinase R like-endoplasmic reticulum kinase (PERK), inositol requiring enzyme 1 (IRE1) and activating transcription factor 6 (ATF6).…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed that, associated to Rhodopsin trafficking defect, key components of the ER stress response were upregulated on the transcriptional level that depicts a common mechanism linked to retinal degeneration in BBS syndromes and LCA, the Bbs1 M390R/M390R mice, Bbs10 −/− mice and Cep290 −/− mice models used herein; although further studies are required to verify this impact on the post-transcriptional level. These mechanisms were also present in Bbs12 −/− mice model, in the Rd16 mouse model; a LCA mice model (Mockel et al, 2012;Starr et al, 2018). In Bbs4 −/− mice models ER stress has not been reported to date even though a Rhodopsin trafficking is already known (Abd-El- Barr et al, 2007).…”
Section: Discussionmentioning
confidence: 97%
“…One of the commonly associated mechanism to photoreceptor apoptosis in the ciliopathies is a defective intraflagellar transport (IFT) of proteins between the two segments (Wright et al, 2010). This defect ultimately causes protein accumulation in the IS, which in turn triggers a proapoptotic unfolded protein response (UPR) associated with an ER-stress (Mockel et al, 2012;Starr et al, 2018). Previously, we have proved that UPR activation occurs in a Bbs12 model, leading us to develop a pharmacological approach (GIVin).…”
Section: Introductionmentioning
confidence: 99%
“…We previously showed that L-Z ameliorated the ERS in the protection against light-induced retinopathy [34]. The rd10 mouse is a RP model with clear characteristics [3538], which carries a missense point mutation in exon 13 of the rod phosphodiesterase 6B ( Pde6b ) gene [36, 37]. The mutations in the same gene also cause human RP [39, 40].…”
Section: Introductionmentioning
confidence: 99%